ANALYSIS OF THE ESSENCE OF “GOVERNANCE MECHANISM” AND BUILDING UP ITS GENERALIZED DEFINITION - Dukov D.F. (Pressing Problems of Public Administration, 2015)
By taking two different methodological approaches, which are based on the defining of thegeneric term, essential features and formal notion of the “system”, the article claims to analyzethe existing definitions of the notion “governance mechanism” and create two new generalizeddefinitions of that notion.